2014
DOI: 10.1097/anc.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hypothermia in NICU Infants

Abstract: Infants admitted to the neonatal intensive care unit (NICU) often require surgical intervention and maintaining normothermia perioperatively is a major concern. In our preliminary study of 31 normothermic infants undergoing operative procedures in the operating room (OR), 58% (N = 18) returned hypothermic while all 5 undergoing procedures in the NICU remained normothermic (P = .001). To describe perioperative thermal instability (temperatures lower than 36.0°C) and frequency of associated adverse events, suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…They also found that hypothermic patients required more cardiac and respiratory interventions than normothermic counterparts. 10 …”
Section: Introductionmentioning
confidence: 99%
“…They also found that hypothermic patients required more cardiac and respiratory interventions than normothermic counterparts. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 3 6 Infants undergoing surgical procedures outside of the NICU have an augmented risk of hypothermia. 7 This risk is due to suboptimal thermal environments within the operating room (OR) and during transportation to and from the OR.…”
Section: Introductionmentioning
confidence: 99%
“… 14 16 One research study investigating the impact of perioperative hypothermia in NICU infants noted that the hypothermic group had significantly more respiratory adverse events ( P = 0.025), were 6 times more likely to require thermoregulatory interventions ( P < 0.001), 5 times more likely to require cardiac support interventions ( P < 0.006), and 3 times more likely to require respiratory interventions ( P = 0.02) than normothermic infants. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Postoperative hypothermia is a recognized complication of anesthesia and surgery in children with many deleterious side effects, including altered coagulation, increased risk of surgical site infections, cardiac dysrhythmias, and apnea [ 1 , 2 ]. The normal physiologic response to hypothermia drives metabolism of fat and shivering.…”
Section: Introductionmentioning
confidence: 99%